THE EFFECTIVENESS AND SAFETY OF BEDAQUILINE-CONTAINING REGIMENS IN THE TREATMENT OF PATIENTS WITH MULTI-DRUG RESISTANT TUBERCULOSIS (MDR-TB): A SYSTEMATIC LITERATURE REVIEW - Miptah Farid Thariqulhaq; Tri Yunis Miko Wahyono (Sean Institute, 2023)
Objective: MDR-TB is a life-threatening infectious disease. In recent years, RR/MDR TB sufferers have increased by 10% from 186,883 patients in 2018 to 206,030 in 2019. The success rate of treatment for RR/MDR-TB patients only reaches 57% globally. WHO has recommended bedaquiline for treatment of MDR-TB as the first drug in an all-oral regimen designed to maximize treatment outcomes. Purpose: to describe the efficacy and safety of a bedaquiline-containing regimen for the treatment of MDR-TB. Methods: Pubmed, Science Direct, and Embase online databases were used to obtain data published in the last five years where literature searches were carried out independently by researchers. The keywords used in this search are combined with the Boolean operator